BIALOSTOSKY, Don. Mikhail Bakhtin. Rhetoric, Poetics, Dialogics, Rhetoricality [Mikhail Bakhtin: retórica, poética, dialógica, retoricalidade]. Anderson, South Carolina: Parlor Press, 2016. 191 p. - Pistori, Maria Helena Cruz (Bakhtiniana. Revista de Estudos do Discurso, 2017)
Resenha